Analisis Yuridis Implikasi Proyek Food Estate Merauke berdasarkan Prinsip SDGs dan Komitmen Net Zero Emission Indonesia - Muhammad Irfan Maulana (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This study analyzes the legal implications of the Merauke Food Estate Project on the principles of sustainable development and Indonesia's commitment to Net Zero Emission (NZE) from the viewpoint of international environmental law. Through a normative legal approach complemented by qualitative empirical analysis, this study reveals that the realization of this project has the possibility of violating national and international environmental principles, which include sustainable development, the precautionary principle, and the polluter pays principle, due to the mass deforestation that increases carbon emissions and the absence of the implementation of the Free, Prior, and Informed Consent (FPIC) mechanism for indigenous peoples. The findings indicate that the legal responsibility of the state and corporations in this project is not fully aligned with Indonesia's commitments under the Paris Agreement and the NZE target. Previously, and Informed Consent (FPIC/PADIATAPA) for indigenous peoples. The findings show that the legal responsibilities of the state and corporations in this project are not completely in line for Indonesia's commitments in the Paris Agreement and the 2060 NZE target, thus requiring policy reconstruction according to a rights-based strategy to ensure a balance between food security, ecological fairness, and a healthy environment.